The influence of protein fractions from bovine colostrum digested in vivo and in vitro on human intestinal epithelial cell proliferation. Issue 1 (16th January 2014) - Morgan, Alison J; Riley, Lisa G; Sheehy, Paul A; Wynn, Peter C
Abstract : Colostrum consists of a number of biologically active proteins and peptides that influence physiological function and development of a neonate. The present study investigated the biological activity of peptides released from first day bovine colostrum through in vitro and in vivo enzymatic digestion. This was assessed for proliferative activity using a human intestinal epithelial cell line, T84. Digestion of the protein fraction of bovine colostrum in vitro was conducted with the enzymes pepsin, chymosin and trypsin. Pepsin and chymosin digests yielded protein fractions with proliferative activity similar to that observed with undigested colostrum and the positive control foetal calf serum (FCS). In contrast trypsin digestion significantly ( P <0·05) decreased colostral proliferative activity when co-cultured with cells when compared with undigested colostrum. The proliferative activity of undigested colostrum protein and abomasal whey protein digesta significantly increased ( P <0·05) epithelial cell proliferation in comparison to a synthetic peptide mix. Bovine colostrum protein digested in vivo was collected from different regions of the gastrointestinal tract (GIT) in newborn calves fed either once ( n =3 calves) or three times at 12-h intervals ( n =3 calves). Digesta collected from the distal duodenum, jejunum and colon of calves fed once, significantly ( P <0·05) stimulated cell proliferation in comparison with comparable samples collected from calves fed multiple times. These peptide enriched fractions are likely to yield candidate peptides with potential application for gastrointestinal repair in mammalian species.